A lactococcal bicistronic vector system for gene delivery and method of preparation thereof - Mat Isa, Nurulfiza; Abdul Rahim, Raha; Mohamed Alitheen, Noorjahan Banu; Abdul Mutalib, Nur Elina (2013)
The present invention provides a bicistronic vector system based on Lactococcus lactis plasmid DNA into which an eukaryotic promoter, a first gene to be transcribed by the promoter, internal ribosome entry (IRES), a second gene to be transcribed by IRES and transcription terminator signal are incorporated in said order downstream of each other. The invention also provides a method of preparation of such vector.